Managing Gall Bladder Perforation in the Setting of Percutaneous Nephrolithotomy – Challenges and Clinical Insights - Nakul Aher; Subash Kaushik TG; Velmurugan Palaniyandi; Hariharasudhan Sekar; Sriram Krishnamoorthy (Newer Frontiers in Urology, Edition 1, 2025)
The preferred treatment for patients with big and complex renal calculi is percutaneous nephrolithotomy (PCNL). Rarely, this surgery can result in visceral damage. Injuries from needle punctures are more likely to occur in a gall bladder (GB) which borders the kidney on the right side. A worse outcome is predicted by GB damage that results in peritonitis. A GB perforation case was described that followed an otherwise unremarkable PCNL and received prompt intraoperative laparoscopic cholecystectomy treatment. The treating surgeon was alerted when the first puncture produced a straw-coloured, gelatinous aspirate. After PCNL, a diagnostic laparoscopy was performed. A bile leak and damage to the gall bladder were discovered. Cholecystectomy was performed electively. The postoperative period was uneventful other than a brief period of paralytic ileus. The patient recovered well and was discharged from the hospital on the third postoperative day. Since early identification can avoid mortality associated with peritonitis and sepsis due to GB perforation during PCNL, it is imperative to be aware of this potentially fatal consequence and to have a high index of suspicion for prompt timely treatment.